Peace through Tourism: A Critical Look at Nepalese Tourism - Upadhayaya, Pranil (Nepal Tourism and Development Review, 2013)
Tourism, the world’s largest and one of the fastest developing economic sectors, virtually affects every region and nation of the world due to its potential contribution to international understanding and poverty reduction. Nepal is no exception. The remarkable growth of tourism at present (peace time) has been progressing through its four progressive theoretical models/platforms (e.g., advocacy, cautionary, adaptancy and knowledge-based platforms) with each having both peace potential and limitation. In this scenario, there is likely growing attention and look at tourism with a passion for its peace prospective. ‘Peace’, a vital and most cherished dream of humanity, is a state that not only indicates the absence of direct violence but also sustains peaceful relationships among all levels and segments of society and between society and nature. Tourism is sensitive to conflict and responsive to peace. There are both opportunities and challenges for the peace responsiveness of tourism in Nepal. Nepalese tourism, which passed through a decade long (1996-2006) armed conflict, serves a concrete illustration of this nexus of tourism and peace with the dual attributes of tourism for conflict and peace. However, this paper envisages that it is a community-based village tourism supported by sustainable structures and actions, backed by proper implementations of tourism regulations, framed with appropriate codes of conduct and materialized by the integrated effort and partnership actions of all (non-scientific and scientific) stakeholders that can be the most viable option for achieving the noble goal of peace through tourism in Nepal. In this context, this paper exemplifies it with an innovative example of a research-linked and empirically executed case of Machhapuchchhre Model Trek (MMT) in Western Nepal. MMT is footed at the knowledgebased platform on transdisciplinary approach in which the scientific (e.g., researchers) and both academic and non-academic (e.g., local communities, local government, tourism practitioners, tourists, etc.) actors approached in an integrated effort to transform local tourism initiatives as peace promoting and conflict mitigating. This paper finally recommends the knowledge-based approach to Nepalese tourism as important not only for bridging the earlier three platforms but also for fulfilling the dual (mass as well as small-scale community-based village tourism) needs of Nepalese tourism at present and thus succeed on peace aspirations through tourism. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7368 Nepal Tourism and Development Review Vol.1(1) 2011 15-40